A major responder to ipilimumab and nivolumab in metastatic uveal melanoma with concomitant autoimmunity. (23rd July 2017) - Chan, Pui Ying; Hall, Peter; Hay, Gordon; Cohen, Victoria M. L.; Szlosarek, Peter W.
Summary: The use of immune checkpoint inhibition has led to major improvements in outcome for patients with metastatic cutaneous melanoma. The combination of ipilimumab and nivolumab has demonstrated greater activity over single‐agent immunotherapy in phase III trials. Clinical trials of combination CTLA‐4 and PD‐1 inhibition are underway in uveal melanoma, for which there are currently no data. Here, we present the case of a 74‐year‐old male patient with metastatic uveal melanoma, who was treated with a combination of ipilimumab and nivolumab. He developed sequential autoimmune transaminitis, diabetes and uveitis, which necessitated discontinuation of maintenance nivolumab 3 months after commencement of treatment. The patient continues to demonstrate an ongoing partial response 10 months from the initial combination immunotherapy, with the evidence of depigmentation of the primary ocular tumour.